Advances in e-business engineering for ubiquitous computing : proceedings of the 16th International Conference on e-Business Engineering (ICEBE 2019) /: proceedings of the 16th International Conference on e-Business Engineering (ICEBE 2019). ([2020]) - Unknown
No abstract available